Extracellular matrix and dermal nerve growth factor dysregulation in prurigo nodularis compared to atopic dermatitis - Deng, Junwen; Parthasarathy, Varsha; Marani, Melika; Bordeaux, Zachary; Lee, Kevin; Trinh, Chi; Cornman, Hannah L.; Kambala, Anusha; Pritchard, Thomas; Chen, Shihua; Sutaria, Nishadh; Oladipo, Olusola O.; et al. (Frontiers in Medicine, 2022)
Prurigo nodularis (PN) is a chronic, pruritic, inflammatory skin disease characterized by hyperkeratotic nodules on the trunk and extremities. While there is growing research on the immunological basis of PN, the neuropathic and structural components of PN lesions are unknown. This study examines the inflammatory, neuropathic, and structural pathways in PN compared to atopic dermatitis (AD) using RNA-sequencing of the lesional and non-lesional skin tissue of PN and AD patients, as well as immunohistochemistry analysis of nerve growth factor (NGF), a neurotrophic factor that regulates nerve development. Transcriptomic analysis of skin biopsies revealed that compared to lesional AD skin, lesional PN skin had significantly increased expression of NGF, matrix metalloproteinases, OSM, MCEMP1, IL1α, IL1β, CXCL2, CXCL5, CXCL8, and insulin-like growth factors in PN compared to AD, and decreased expression of CCL13, CCL26, EPHB1, and collagens (COL4/6). Gene Set Enrichment Analysis demonstrated higher enrichment of keratinization, cornified envelope, myelin sheath, TGF-beta signaling, extracellular matrix disassembly, metalloendopeptidase activity, and neutrotrophin-TRK receptor signaling pathways in PN. On immunohistochemistry, PN lesions demonstrated higher dermal NGF expression compared to AD. We present novel findings demonstrating increased neurotrophic and extracellular matrix remodeling signatures in PN compared to AD, possibly explaining the morphological differences in their lesions. These signatures may therefore be important components of the PN pathogenesis and may serve as therapeutic targets.